Interactions : transregional perspectives on world history - Bentley, Jerry H., 1949-2012; Bridenthal, Renate; Yang, Anand A. (Perspectives on the global past., 2005)
The essays presented here reflect recent widespread interest in reconsidering the political, geographical, and cultural boundaries conventionally observed by area specialists and others. They intentionally range widely through time and space, dealing with diverse issues and contexts, but each highlights the very general theme of cross-cultural interaction. Although they draw heavily on area studies, the contributors seek to put previously separate bodies of scholarship in dialogue with one another by exploring those interactions that have historically linked world regions. Four general themes are especially prominent in this volume, and the essays develop sophisticated positions on each. On the issue of agency and structure, they offer useful guidance toward recognizing the importance of both human agency and historical structures in historical processes. On the theme of states and their roles in cross-cultural interactions, they acknowledge that states do not entirely control their own destinies but nevertheless deeply influence the development of these exchanges, sometimes decisively so. Regarding the theme of the global and the local, they emphasize the reciprocal influence of global dynamics and local circumstances and agree that analyses must take both into account to be successful. Finally, all of the essays allow that the theme of cross-cultural interaction is crucial to understanding the world and its development through time. Contributors:C. A. Bayly; Sven Beckert; Jerry H. Bentley; Renate Bridenthal; Charles Bright; Michael Geyer; Alan L. Karras; Adam McKeown; Colin Palmer; Stephen H. Rapp, Jr.; Caroline Reeves; John O. Voll; Kären Wigen; Anand A. Yang.